Detection of endosymbiotic, environmental, and potential bacterial pathogens in diverse mosquito taxa from Colombian tropical forests using RNAseq - Robayo-Cuevas, Cristian; Junca, Howard; Uribe, Sandra; Gómez-Palacio, Andrés (Frontiers in Microbiology, 2025)
IntroductionMosquitoes of the subfamily Culicinae transmit pathogens of major medical and veterinary importance, particularly in tropical regions where urbanization and ecological change promote arbovirus circulation. In Colombia, rural Culicinae species are diverse and harbor microbiomes that may influence vector competence, yet their bacterial communities remain poorly characterized.MethodsWe characterized the bacterial microbiota of multiple Culicinae species and morphotypes collected from two rural localities in Antioquia, Colombia, using an integrated metagenomic approach. Ribosomal 16S rRNA sequences were extracted from total RNA-seq datasets to infer bacterial community composition and assess α- and β-diversity. Diversity metrics (Chao1 and Shannon indices), Discriminant Analysis of Principal Components (DAPC), and Bray–Curtis ordination were used to evaluate community structure. In parallel, de novo assembled contigs were taxonomically annotated against the NCBI NR bacterial database to obtain complementary taxonomic and functional insights.ResultsCulex morphotypes exhibited the highest richness and evenness, whereas Aedes and Trichoprosopon showed lower diversity. Ordination and DAPC analyses revealed partial clustering by species and tribe. Both the 16S and assembly-based analyses showed complex bacterial assemblages dominated by Wolbachia (up to 60% of reads in several Aedes and Culex morphotypes), followed by environmental genera such as Pseudomonas and Acinetobacter (10–20%). Lower-abundance taxa of medical and veterinary importance—including Salmonella, Borrelia, and Clostridium (<5%)—were also detected. Bacterial community structure differed among mosquito species; Aedes albopictus was enriched in lactic acid bacteria, while Culex morphotypes exhibited broader environmental and endosymbiotic profiles.DiscussionThis study provides the first comprehensive metagenomic description of bacterial communities associated with rural Culicinae mosquitoes in Colombia. The predominance of symbionts such as Wolbachia and Spiroplasma, coupled with distinct bacterial signatures among host species, highlights the ecological complexity of these microbiomes and their potential relevance for microbiome-based strategies in sustainable arboviral disease management.